Pendampingan Belajar 'Darul Ilmi' untuk Meningkatkan Motivasi Anak Usia Madya - Abdullah; Moh. Ainol Yaqin; Wildana Dwi Lestari (Yayasan Literasi Altruis Khatulistiwa, 2025)
The “Darul Ilmi” tutoring program in Kedungrejo Village, Bantaran Subdistrict, Probolinggo Regency aims to enhance the learning motivation of middle childhood students who face various challenges in formal education. The main issues in this village include low interest in learning, limited access to tutoring services, and lack of parental support in the children's learning process. These problems contribute to low academic achievement among students. As a form of community service, the “Darul Ilmi” program was designed to address these challenges through a comprehensive non-formal educational approach. Activities include regular tutoring sessions using interactive and personalized methods, delivery of supplementary materials tailored to students’ needs, and moral support to foster learning enthusiasm. The approach combines pedagogical and motivational elements in a holistic manner. Evaluation results show that participating children demonstrated improved motivation, became more active in school, and achieved better academic performance. This program proves that structured tutoring outside of school can have a significant positive impact on the educational development of children in underserved areas with limited formal education support